Introducing the OECD guidance document on occupational biomonitoring: A harmonized methodology for deriving occupational biomonitoring levels (OBL) - Hopf, Nancy B.; Bessems, Jos; Santonen, Tiina; Viegas, Susana; Casteleyn, Ludwine; Poddalgoda, Devika; Lamkarkach, Farida; Göen, Thomas; Zare Jeddi, Maryam; Koller, Michael; Rousselle, Christophe; Jones, Kate; et al. (Toxicology Letters, 2025)
Derivation of occupational biomonitoring levels (OBLs) is needed to effectively utilize biomonitoring for assessing exposures to chemical substances, and consequently, implement risk reduction measures to reduce health risks among workers. OBLs are the appropriate option for chemical substances that can be absorbed through the skin. This methodology for derivation of OBLs has been developed in collaboration with scientific and regulatory experts from more than 40 institutes in 15 countries within the Organization for Economic Cooperation and Development (OECD) framework. This manuscript provides a summary of the guidance on derivation of OBLs destined for scientists, risk assessors, and regulators who are tasked with establishing OBLs for regulatory purposes and implementing occupational biomonitoring programs. The derivation methodology follows a tiered approach based on the strength of evidence and quality of the data that we have labeled level of confidence. The tiered approach serves as a practical framework in occupational health risk assessment and management. We distinguish between four OBL levels depending on the strength of scientific evidence and confidence level: health-based derivation of OBL based on robust epidemiological data showing causal exposure-health effect relationship and Provisional OBL (POBL) based on robust toxicological animal data showing dose-response relationship as well as two assessment values which are not health based: reference levels in the general population (Reference OBL or (ROBL)), and Technical achievable OBL or (TOBL). Four case studies illustrating the derivation methods for OBLs and POBLs are also provided. Using this state-of-the-art approach (OECD guidance document no. 370) will lead to a harmonized derivation of OBLs and subsequently to evidence-based risk management measures.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Biomonitoring; Harmonized methodology; Human; Occuaptional exposure assessment; Occupational biomonitoring levels; OECD